THE SYMBOLIC REPRESENTATION OF ULOS IN BATAK CULTURE: AN ECOLINGUISTIC PERSPECTIVE - Hariati, Puji; Purwarno, Purwarno (University of Kuningan, 2024)
This research investigates the symbolic representation of the ulos in Batak culture from an ecolinguistic perspective, highlighting its role as a cultural artifact deeply intertwined with language, tradition, and the environment. Using a descriptive qualitative approach, data were collected through interviews with weavers, Raja Perhata (cultural experts), and traditional leaders who possess deep knowledge of the ulos. The study focuses on specific Toba Batak ulos, such as Ragi Hidup, Ragi Hotang, and Sibolang, each symbolizing unique aspects of Batak values and worldviews. Ragi Hidup conveys blessings for happiness, offspring, and longevity, particularly during wedding ceremonies, while Ragi Hotang is associated with respect and honor, and Sibolang signifies the act of paying homage. These symbolic meanings are intricately embedded in the patterns, colors, and material composition of the ulos, reflecting their significance in Batak society. The findings reveal that the ulos is not merely a textile but a vessel of cultural meaning, encompassing prayers for prosperity, social status, and well-being. Through the lens of ecolinguistics, this study demonstrates how the ulos, as a cultural symbol, contributes to the sustainability of Batak traditions by encoding and perpetuating ecological and social values within its symbolic framework. The research underscores the critical importance of preserving these traditional symbols to maintain the cultural heritage and identity of the Bataknese people while offering broader insights into the role of language and culture in sustaining community values.